2006
DOI: 10.7326/0003-4819-145-10-200611210-00007
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics: Challenges and Opportunities

Abstract: Requests for Single Reprints:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
136
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(141 citation statements)
references
References 79 publications
(71 reference statements)
0
136
1
Order By: Relevance
“…Moreover, refinement and further improvement of the prediction model are warranted. Additional research may also focus on the contribution of other factors such as inflammatory cytokine levels, because variability in drug response may also reflect changes in the complex biologic milieu in which drugs interact with their target molecules (53).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, refinement and further improvement of the prediction model are warranted. Additional research may also focus on the contribution of other factors such as inflammatory cytokine levels, because variability in drug response may also reflect changes in the complex biologic milieu in which drugs interact with their target molecules (53).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, all possible pairwise SNP comparisons were used to compute R 2 and D′ values [25]. Data for all pairwise SNP comparisons with R 2 values ≥ 0.7 are listed in Supplemental Table 3.…”
Section: Linkage Disequilibrium and Haplotype Analysismentioning
confidence: 99%
“…Moreover, it is likely that in the future a panel of genetic markers, or even a whole-genome scan, will form the basis of treatment tailoring, potentially leading to a stronger benefit of tailored therapy. 29,48 Third, the effects of discounting across time and the modest survival benefits of increasing the 6-month quit rate lead to clustering of the mean cost and LY outcomes, and consequently our comparisons are sensitive to model parameters and assumed costs when varied in combination. In some cases, the differences between treatments were too small to distinguish statistically even with the large number of subjects we simulated, leading to ambiguity in the determination of which treatments are dominated.…”
Section: Discussionmentioning
confidence: 99%
“…27 Nevertheless, it is understood that the cost-effectiveness of a genetically tailored drug treatment plan will depend on a number of factors: the distribution of the relevant genetic variants, the costs of genetic testing and subsequent treatment and the effectiveness of the tailored therapy compared to a 'one-size-fits-all' approach. 28,29 In this article, we describe a model of tobacco dependence treatment that allows us to simulate cost and effectiveness outcomes to assess the value of pharmacogenetic testing using data on pharmacogenetic effects observed in tobacco dependence treatment trials. 7 Estimates of pharmacogenetic effects in these trials are within the range of those observed for a variety of psychiatric medications.…”
Section: Introductionmentioning
confidence: 99%